Problematika Pengelolaan Sampah Desa Dalam Kerangka Kewenangan Lokal Bersekala Desa (Tinjauan Yuridis di Desa Kembang Mekar Sari Kabupaten Indragiri Hilir) - Masyduki; Jamri; Kms. Novyar Satriawan Fikri (PT PUSTAKA CENDEKIA GROUP, 2026)
Waste management is part of the local authority at the village level within the framework of village autonomy. However, the implementation of waste management in Kembang Mekar Sari Village, Indragiri Hilir Regency, still faces various obstacles, both legal and factual. This study aims to determine the regulation of village authority in waste management, analyze the problems faced by the village government, and examine legal and policy efforts in optimizing waste management. This study used an empirical legal research method with a sociological legal approach. Data were obtained through literature review and interviews, then analyzed descriptively and qualitatively. The results indicate that village authority in waste management is regulated in Law Number 6 of 2014 concerning Villages and other related regulations. However, its implementation has not been optimal due to the absence of Village Regulations on waste management, low public awareness, limited facilities and infrastructure, and minimal budget support. Possible measures include the establishment of Village Regulations, increasing community participation, strengthening waste management institutions, and collaborating with local governments to create a clean and sustainable village environment.